A obra de Garoto para violão: o resultado de um processo de mediação cultural - Humberto Junqueira (2010)
This paper attempts to verify the results of Garotos life as an artist who enabled a process of cultural mediation. You will see an investigation that analyzes the way he interacts and moves along different cultural spectrums, whereas his pieces for acoustic guitar are observed from the point of view of their dialogues with the plurality of the Brazilian culture. In order to do that, we look into the traditions where he belongs, resorting to theories that allow us to consider the cultural crossings that he had been involved. We are also interested in the different interpretations and meanings assigned to popular music as part of the Brazilian culture, as well as the various activities played out by Garoto throughout his career.